Field trials of an improved cost-effective device for detecting peridomestic populations of Triatoma infestans (Hemiptera: Reduviidae) in rural Argentina - Vazquez Prokopec, Gonzalo Martin (2002)
An improved device for detecting peridomestic Triatoma infestans consisting of one-liter recycled Tetra Brik milk boxes with a central structure was tested using a matched-pair study design in two rural areas in Argentina. In Olta (La Rioja), the boxes were installed beneath the thatched roofs and on the vertical wooden posts of each peridomestic structure. After a 5-month exposure, at least one of the recovered boxes detected 88% of the 24 T. infestans-positive sites, and 86% of the 7 negative sites by timed manual collections at baseline. In Amamá (Santiago del Estero), the boxes were paired with the best performing prototype tested before (shelter unit). After 3 months, some evidence of infestation was detected in 89% (boxes) and 79% (shelters) of 18-19 sites positive by timed collections, whereas 19% and 16% of 32 negative sites were positive, respectively. Neither device differed significantly in the qualitative or quantitative collection of every sign of infestation. The installation site did not modify significantly the boxes' sampling efficiency in both study areas. As the total cost of each box was half as expensive as each shelter unit, the boxes are thus the most cost-effective and easy-to-use tool for detecting peridomestic T. infestans currently available.